Self-Similarities in Gender Inequality and Human Freedom - Del Rosario, Ann Sheila (Social Sciences and Development Review, 2019)
This study utilized the data of countries worldwide to explore on their fractal distribution vis a vis gender inequality and freedom. It determined whether gender inequality can be enhanced via exercise of unrestrained human freedom. The gender inequality index used in this study measures gaps in reproductive health, empowerment and the labor market while human freedom is measured on the basis of civil liberties and political rights. Results of the fractal dimension estimates of the variables which are 1.92661 and 1.29979 respectively denote that human freedom accounts for the 61% of the gender inequality among countries included in the study. This finding suggests that the exercise of some sort of freedom can in itself create some sort of gender inequality. Overall, the results provide further evidence that the characteristics of gender inequality phenomenon is true to all countries including those countries who are completely free and who have relatively competitive and advanced economies.